Siti Rahma Kumala Dewi Pengaruh Kebijakan Dividen dan Struktur Modal terhadap Harga Saham di Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia - Siti Rahma Kumala Dewi (Accounting Department UNUSIA, 2023)
This study aims to determine the effect of dividend policy (DPR) and capital structure (DER) on stock prices in manufacturing companies on the Indonesian stock exchange either partially or simultaneously. The data in this study were obtained from the Indonesian Stock Exchange, which is willing to be a respondent. This study uses a quantitative research approach. The sample used is the annual financial statements for the period 2012-2014. Quantitative data analysis method by conducting research directly in the field. By taking the data used is multiple linear regression analysis which is processed using SPSS 20. The research results show that. Partially, dividend policy has no significant positive effect on stock prices and capital structure and has a significant negative effect on stock prices.